Profile of animal bite cases at immune prophylaxis clinic, tertiary care centre - Bhise, Jyoti Dattaramji; Bhise, Swati Dattaramji (International Journal Of Community Medicine And Public Health, 2017)
Background: Animal bite, one of the common causes of physical injuries in spite of a long standing nature of the dog bite problem and the presence of effective intervention strategies for rabies control, it continues to pose a major public health challenge to program planners. So the present study is conducted to study Profile of animal-bite cases at immuno-prophylaxis clinic, at tertiary care centre. Methods: The present study was an observational cross-sectional study carried out at immune prophylaxis clinic of tertiary care centre, from 1st January 2013 to 31st December, 2013. All the registered cases of animal bite attending immune-prophylaxis clinic, which are ready to participate in the study were included as study population. The method used was systematic random sampling. First case was selected randomly using lottery method and then every fifth case reporting to immune prophylaxis clinic was taken in the study group. Total 3504 cases of animal bite were reported during the study period. 20% of these i.e. 700 cases of animal bite were included in the study. Results: Out of 700 study subjects, highest number of bites occurred in the age group 21-30 years i.e. 155 (22.1%). Maximum study subjects 471 (67.3%) were from urban area and 53% of bites occurred during daytime. Maximum cases were the class-III bite i.e. 600 (85.7%). Conclusions: Maximum number of bites seen among 21-30 years of age group predominantly seen among male study subjects. 49.6% study subjects were bitten by pet animals and 47.6% were bitten by stray animals. Dog was the principle animal responsible for the bite of study subjects. 85.7% of study subjects were of class III bite among them 75% study subjects had reported to hospitals within 24 hours. Severe the degree of exposure, earlier was reporting to the hospital was statistically significant.